Investigando os efeitos do ensino de tato na aquisição e manutenção de um pequeno vocabulário em língua estrangeira - Lima, Marcelo Afonso Keller Ferreira (Universidade Federal de São Carlos, 2024)
Studies in the field of a second-language acquisition have shown the efficiency of tact instruction procedures in producing emergent verbal responses. The aim of the study was to investigate the effects of tact instruction on the acquisition and maintenance of a small vocabulary in a foreign language (english) for different sets of stimuli taught successively, evaluating the emergence of responses not taught directly (bidirectional intraverbal responses) and the effects of successive instruction of different sets of stimuli on the learning curve. Three Brazilian children with typical development participated. The participants were taught to tact in English (foreign language) and intraverbal responses were tested in both native-to-foreign (NF) and foreign-to-native (FN) directions before and after the teaching conditions. A multiple probe design between stimulus sets was adopted. Maintenance data was collected 15 days after the end of the study. The results showed emergence of bidirectional intraverbal responses for all participants after teaching condition and acceleration in the learning curve for two of the three participants, indicating the occurrence of learning-set effects. The results replicate and expand on the findings presented in the literature in this field. The implications of this study for future research on the second-language acquisition in addition to the emergence of responses not directly taught are discussed.
Investigating the effects of tact instruction on the acquisition and maintenance of small foreign language vocabulary
Keywords: Relações emergentes; Tato; Intraverbal; Segunda língua; Learning-set; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL